Negative-Sequence Active and Reactive Currents Compensation for Unbalanced Three-Phase Networks Subject to Various Line Impedance Attributes - Chen, Woei-Luen; Su, Yung-Hang (IEEE journal of emerging and selected topics in power electronics, 2022)
In three-phase systems, voltage unbalance is incurred mainly by load unbalance under balanced lines. Based on the identical line impedance attributes between any two phases, a region of compensation (RoC) describing the relationship between the negative-sequence current vector and the line impedance attribute was presented. The RoC derivation arose primarily from the negative-sequence voltage across the equivalent source impedance. However, the source impedance attribute might be different between phases due to the embedded unbalanced load. A conversion from the source impedance to the line impedance was performed such that the mapping between the RoC and the impedance attribute becomes meaningful. The RoC is beneficial in narrowing the search and therefore simplifies the algorithm for determining the negative-sequence active and reactive current commands for a static synchronous compensator (STATCOM). To alleviate the current burden, the minimal voltage drop across the line impedance and a current weighting with safety boundary was incorporated. A quadrant of convergence (QoC) concluded from the experimental results agrees with the RoC and shows the effectiveness of the proposed approaches.